THE QUALITY IMPROVEMENT OF THE VENTILATION SYSTEM OF PASSENGER CARS IN OPERATION - Shmakov, S. V.; Rechkalov, S. D. (Science and Transport Progress, 2007)
The modern cars passenger compartments have the blank windows; there is no also natural ventilation in compartment. In these conditions, the role of qualitative and reliable work of cars ventilation grows during the time operation. In article new approaches during and carrying out of modernization control systems in passenger spaces of the rolling stock are offered.